PKM Pembuatan Akuaponik di Kelurahan Mekar Baru Kabupaten Asahan - Putra, Pasca Dwi; Frisnoiry, Suci; Thohiri, Roza; Budiarta, Kustoro (Yayasan Rahmat Islamiyah, 2025)
Asahan Regency's capital, Mekar Baru Sub-district, has a low number of agricultural laborers and a small amount of land, which would affect the rising and costly demand for food in cities. The issues identified by the partners include a lack of expertise in hydroponic vegetable and catfish farming. As a result, partners in hydroponic vegetable and catfish production require help. Assistance and training in aquaponic vegetable and catfish farming, as well as the creation of aquaponics systems and the provision of vegetable and catfish seeds, have been conducted as part of this program.